Visible light-promoted, photocatalyst-free decarboxylative alkylation of 2H-indazoles via electron donor–acceptor complex activation. (10th August 2022) - Wang, Jin; Song, Qingyuan; He, Xing; Ma, Chunhua; Jiang, Yuqin; Fan, Jing
Abstract : A transition metal-free, traditional dye-free, and visible light-promoted reaction to achieve the direct alkylation of 2 H -indazoles. Abstract : A transition metal-free and traditional dye-free visible light-driven direct alkylation of 2-aryl-2 H -indazoles was developed in the catalytic system of an electron donor–acceptor (EDA) complex involving alkyl N -hydroxyphthalimide (NHPI) esters, triphenylphosphine (PPh3 ), and sodium iodide (NaI).